The Relationship between Live Streaming and Consumers’ Purchase Intention in Perak - Ong Yen Yen,; Juzaimi Nasuredin, (Research in Management of Technology and Business, 2024)
Live-streaming services have been adopted as a direct marketing method by many small individual sellers. The emergence of the COVID-19 epidemic has brought about a trend toward online shopping, creating consumer interest in new online shopping habits. Most previous studies have focused on consumers' purchasing behavior towards e-commerce live streaming and online shopping, but these studies still need clarification. This study investigates the relationship between live streaming and consumers' purchase intention in Perak. The objective is to determine the level of live streaming and the level of consumers’ purchase intention and investigate the relationship between live streaming and consumers’ purchase intention in Perak. This study used the Theory of Planned Behavior (TPB) model as a theoretical foundation. The data have been collected by distributing survey questionnaires to Perak consumers using a quantitative method. 384 questionnaires have been distributed online to Perak consumers via Google Forms. There were 286 questionnaires returned and analyzed using the Statistical Package for the Social Sciences (SPSS) version 27. The analysis shows that all the hypotheses are achieved at Spearman’s rho correlation test. This study found a positive and significant relationship between the independent variables (live streaming, such as streamer’s credibility, media richness, and interactivity) and the dependent variable (consumers’ purchase intention). Therefore, this study has provided valuable insights for online marketers and future academic researchers to understand the relationship between live streaming and consumers’ purchase intention.